Overkilt - Dunnett, Kaitlyn (Dunnett, Kaitlyn. Liss MacCrimmon mystery., 2018)
"Liss MacCrimmon's meddlesome mother is back in Moosetookalook, Maine, to serve a hefty portion of trouble in time for Thanksgiving. But when a scandalous murder case threatens to leave Liss alone at the table, family drama takes on a terrifying new meaning . . . While Liss preps the Scottish Emporium for November's inevitable shopping rush, other local businesses aren't half as lucky. Year after year, her father-in-law's rustic hotel can barely turn a profit during the stretch between autumn's peak and ski season. Except this time, Mr. Ruskin realizes that the recipe for success lies in enticing an untapped niche clientele--childless couples desperate for a holiday away from family . . . The unusual marketing tactic has everyone in Moosetookalook talking. Unfortunately, it also inspires a scathing social media campaign aimed at persuading tourists to boycott the hotel for affronting family values. Liss dismisses the bad publicity as being totally "overkilt"--until angry mobs fill the streets, the troublemaker who started it all turns up dead, and her loved ones are suspected of murder . . . With so much at stake, Liss can't possibly follow police orders to stay out of the investigation. There's just one wee problem: saving her own clan could mean sending a friend or two behind bars. Now--partly helped, partly hindered by her difficult mother--Liss must digest a slew of unsettling clues and catch the real killer . . . or else everything she's ever been thankful for may vanish before her eyes."--Provided by publisher.